An Update of Murrayan Needs: A Pilot Study Among American College Students. (January 2014) - Xu, Xiaoyan; Mellor, David; Xu, Yangang; Duan, Liqiong
Much research work on motives has been based on the taxonomy of psychogenic needs originally proposed by Murray and his colleagues in 1938. However, many of these needs have received little attention, and some of them may be less relevant now than they were 70 years ago. Two studies were conducted to investigate current motives. In Study 1, we used the Striving Assessment to elicit the personal strivings of 255 undergraduate university students. Murray's taxonomy was unable to account for 50% of the 2, 937 strivings. These strivings were thematically groups into 11 new categories and combined with 7 Murrayan needs to form the Comprehensive Motivation Coding System (CMCS). In Study 2, Thematic Apperception Test (TAT) stories produced by 143 undergraduate student participants were coded by these two systems. Murray's system was unable to fully account for 42% of motives identified in the TAT stories, but the CMCS was able to account for 89%. These findings suggest that Murrayan needs may not adequately describe contemporary motivations and that the CMCS has the potential to do so. However, due to the limited demographics of our sample, further investigations are needed.